2007
DOI: 10.1001/archopht.125.5.671
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Dietary Lipid Intake and Age-Related Macular Degeneration in a Case-Control Study

Abstract: Age-Related Eye Disease Study Research Group* Objective: To evaluate the association of lipid intake with baseline severity of age-related macular degeneration (AMD) in the Age-Related Eye Disease Study (AREDS). Methods: Age-Related Eye Disease Study participants aged 60 to 80 years at enrollment (N = 4519) provided estimates of habitual nutrient intake through a selfadministered semiquantitative food frequency questionnaire. Stereoscopic color fundus photographs were used to categorize participants into 4 AMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(111 citation statements)
references
References 11 publications
5
96
2
1
Order By: Relevance
“…AMD is a complex disease, with both environmental (e.g., diet and smoking) (Age-Related Eye Disease Study Research Group, 2001; Seddon et al, 1994, 2001b; Christen et al, 1996; SanGiovanni et al, 2007; Seddon et al, 1996; Vingerling et al, 1996) and genetic risk factors. The notion that AMD is an inherited disease was discussed at least as early as the 1970s, when Gass noted the similarities between clearly familial drusen and “senile” drusen (Gass, 1973).…”
Section: Genetics Of Amdmentioning
confidence: 99%
“…AMD is a complex disease, with both environmental (e.g., diet and smoking) (Age-Related Eye Disease Study Research Group, 2001; Seddon et al, 1994, 2001b; Christen et al, 1996; SanGiovanni et al, 2007; Seddon et al, 1996; Vingerling et al, 1996) and genetic risk factors. The notion that AMD is an inherited disease was discussed at least as early as the 1970s, when Gass noted the similarities between clearly familial drusen and “senile” drusen (Gass, 1973).…”
Section: Genetics Of Amdmentioning
confidence: 99%
“…In fact, clinical prospective and questionnaire studies have revealed that dietary intake of lutein, zeaxanthin, and fruits rich in antioxidants decreases the incidence of neovascular AMD [63], while a low plasma level of zeaxanthin is associated with increased risk of developing early AMD [69]. The landmark AREDS clinical trial showed that oral daily supplementation with the antioxidants zinc, copper, vita-min C, vitamin E, and beta-carotene significantly reduced the risk of developing advanced AMD in participants with intermediate AMD in at least one eye [70]. The follow-up randomized, double-masked, placebo-controlled clinical trial, AREDS2, determined whether or not adding supplements containing lutein/zeaxanthin or the omega-3 PUFAs, docosahexaenoic acid (DHA)/eicosapentaenoic acid (EPA), or both, to the AREDS formulation decreases the risk of developing advanced AMD.…”
Section: Etiology Of Amdmentioning
confidence: 99%
“…This association was observed when fish intake frequency was >1 serving/week. An inverse association between intake of DHA/EPA and AMD progression was also observed [1921,23]. Studies with different intake amounts of DHA and EPA (1, 0.35, 0.06 g/day, ≥64.0 or ≥42.3 mg/day) showed that a higher intake of DHA or EPA correlates with a decreased risk of AMD compared with a lower intake.…”
Section: The Role Of Lc- and Vlc-pufas In Macular Degenerationmentioning
confidence: 92%
“…Relative to RPE, the amount of AA in rod outer segments (ROS) was 4–16 times lower, and the highest concentrations of AA in human retina are found in phosphatidylcholine (PC) and phosphatidylethanolamine (PE). AA values in RBC lipids were significantly higher in AMD patients than in controls [27], and dietary AA was directly associated with NV-AMD prevalence [19,20]. However, AA levels were significantly lower in the plasma phospholipids of patients with Usher’s syndrome, an inherited autosomal recessive disorder characterized by deafness and visual cell degeneration similar to retinitis pigmentosa [63].…”
Section: The Role Of Lc- and Vlc-pufas In Macular Degenerationmentioning
confidence: 99%